O que provoca o encontro das crianças com as artes na educação infantil? Essa é fácil Breno, a gente é tudo diferente! - Almeida, Breno Alvarenga (2020)
Working with Arts as an area of knowledge still in early childhood education is very important since it allows children, who are playing beings, developing critical thinking, cognitive, and even physical aspects. Besides, Arts can enable numerous questions to be raised considering the context to which children are inserted. Given this context and the (trans)formations that intertwine life-art and art-life, the present research, which is configured as being qualitative and based on post-structuralist references, aims: to investigate whether working with the Arts allows problematizing issues related to the production of identities and differences in the context of early childhood education. Aligned to this, there is a research problem: what reflections working with Arts can trigger in young children? Is it possible to address issues such as diversity, identities, and differences? Thus, starting from the point that when conducting researches with children it is necessary to do it with the children and not on them, the children participating in this work are aged between 4 and 5 years old and attended the first and second stage of early childhood education in a multigrade class from a school institution located in the countryside, in Lavras city - Minas Gerais state. The empirical material was obtained through classes-workshops previously elaborated from scripts. Resources such as filming and photography were later used to report the activities carried out, the children's expressions and speeches, as well as to analyze the works of art produced by the target audience of the research. The classes-workshops held were developed based on the Triangular Approach to Teaching Arts and took place after two days of a first approach of the class through participant observations. In light of this, this proposal is justified by the fact that although they occupy the same space and remain together, the subjects perceive themselves different in a process of signifying their identity, which is constructed as a reference to be followed and, on the other hand, the difference is annihilated, deleted. As a result, it was possible to identify that, through the Arts, it is possible to problematize numerous issues with children who move through themes such as gender, sexuality, race, ethnicity, differences, among others.